Algunas precisiones sobre la incidencia de la política de concentración parcelaria en Aragón - De La Riva Fernández, Juan (Geographicalia, 2017)
This work entails a first assessment about the repercussion in Aragon of the Land Consolidation policy. Its temporal evolution is analysed attending to the different stages in the process of consolidation. Completed zones and its significance by provinces are considered with some detail. The current state of Land Consolidation works, locating the Aragonese case in its national context and apporting some index and calculus are presented. Finally, the percentage of affected by the Land Consolidation process areas, at a municipal level, is shawn in a map.